1980
DOI: 10.1093/nar/8.17.4021
|View full text |Cite
|
Sign up to set email alerts
|

Serine activation is the rate limiting step of tRNASeraminoacylation by yeast seryl tRNA synthetase

Abstract: Using the quenched flow technique the mechanism of seryl tRNA synthetase action has been investigated with respect to the presteady state kinetics of individual steps. Under conditions where the strong binding sites of the enzyme are nearly saturated and the steady state turnover number is about 1 s-1, rate constants of four different processes have been determined: steps connected with substrate associations are relatively slow (12 s-1 for the entire process); activation of serine is the rate determining step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…The rate is stimulated in the presence of Blank values as measured in the absence of serine were subtraced. Evaluation of the curves yielded the initial rate of serine activation in the absence of tRNA Ser and tlre steady state rate of ATP hydrolysis in the presence of tRNA Set which is practically equal to the rate of serine activation under this condition [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate is stimulated in the presence of Blank values as measured in the absence of serine were subtraced. Evaluation of the curves yielded the initial rate of serine activation in the absence of tRNA Ser and tlre steady state rate of ATP hydrolysis in the presence of tRNA Set which is practically equal to the rate of serine activation under this condition [13].…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of relaxation kinetic studies on tRNA Set dissociation from SRS [ 11 ] the stimulating effect of KCl was explained by a salt4nduced acceleration of seryl-tRNA Set dissociation [12]. However, recent investigations [13] revealed that SRS differs from other aminoacyl-tRNA synthetases in that the activation of serine is the rate limiting step of tRNA Set aminoacylation and not the dissociation of the seryl-tRNASer-sRS complex. We therefore have examined the question further and found the serine activation to occur much faster in the absence than in the presence of tRNA Ser.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed pre-steady-state analysis of mutants of tRNA His or HisRS compromised with respect to tRNA identity suggested that, in the complete aminoacylation reaction, formation of aminoacyl adenylate in the second active site is contingent upon a productive aminoacyl transfer reaction in the first (20). These and other data led to the proposal of an alternating site model for HisRS (20) that is analogous to the "flip flop" catalysis suggested for class II PheRS (21,22) and class Ic TrpRS (14). This raises the possibility that the catalytic cycles of dimeric class II enzymes and dimeric class Ic enzymes share some common feature.…”
Section: Reactionmentioning
confidence: 95%
“…It has been reported that inorganic pyrophosphate inhibits Ap 4 A synthesis by aminoacyl-tRNA synthetases through competitive inhibition of the ATP reaction with aminoacyl-adenylate [8,21]. To confirm whether inorganic pyrophosphate inhibits the Ap 4 A synthase activity of LysS, LysS was incubated with inorganic pyrophosphate in the presence of 5 mM ATP.…”
Section: Lyss Exhibits Ap 4 a Ap 3 A And Adp Synthase Activitiesmentioning
confidence: 99%